Shape programming of liquid crystal elastomers - Andraž Rešetič (Communications Chemistry, 2024)
Abstract Liquid crystal elastomers (LCEs) are shape-morphing materials that demonstrate reversible actuation when exposed to external stimuli, such as light or heat. The actuation’s complexity depends heavily on the instilled liquid crystal alignment, programmed into the material using various shape-programming processes. As an unavoidable part of LCE synthesis, these also introduce geometrical and output restrictions that dictate the final applicability. Considering LCE’s future implementation in real-life applications, it is reasonable to explore these limiting factors. This review offers a brief overview of current shape-programming methods in relation to the challenges of employing LCEs as soft, shape-memory components in future devices.